Analysis of Adaptability Level Towards Employees’ Learning Agility in Dealing with New Technology with Gender as Moderation at PT. Marugo Rubber Indonesia - Enzelia Umu Rahmawati; Mohammad Darul Fadli, Uus; Rosmawati, Ery; Prayudo, Gito (Research in Management of Technology and Business, 2025)
This study was conducted at PT Marugo Rubber Indonesia, an automotive manufacturing company based in Karawang, which is facing challenges in adapting to digital transformation, especially in implementing a digital-based inventory system. This change requires employees to have a high Adaptability and Learning Agility level. This study aims to analyze the effect of Adaptability on Learning Agility in dealing with new technology at PT Marugo Rubber Indonesia, with gender as a moderating variable and using a quantitative method with SmartPLS4 with the Structural Equation Modeling (SEM) tool. The sample used was 100 employees from a total population of 276 people. The results showed that Adaptability significantly affected Learning Agility (R² = 0.709), where cognitive flexibility and mental agility were the leading indicators. However, gender was not proven to moderate the relationship. The conclusion of this study confirms that the success of technology adaptation at PT Marugo Rubber Indonesia depends more on a work environment that supports employee learning and flexibility than on gender factors. Therefore, companies should develop training programs that improve employee readiness for technological change